X2+10x+25y2+25
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\left(x^3-x^2+x\right)\left(121-25y^2-10y\right)-\left(x^3-x^2+x\right)-\left(121-25y^2-10y\right)+1\)
\(=\left(x^3-x^2+x\right)\left(120-25y^2-10y\right)-\left(120-25y^2-10y\right)\)
\(=\left(120-25y^2-10y\right)\left(x^3-x^2+x-1\right)\)
\(=-\left[\left(25y^2+10y+1\right)-121\right]\left[x^2\left(x-1\right)+\left(x-1\right)\right]\)
\(=-\left(5y-10\right)\left(5y-12\right)\left(x-1\right)\left(x^2+1\right)\)
\(=-5\left(y-2\right)\left(5y-12\right)\left(x-1\right)\left(x^2+1\right)\)
b: \(x^4-14x^3+71x^2-154x+120\)
\(=x^4-5x^3-9x^3+45x^2+26x^2-130x-24x+120\)
\(=\left(x-5\right)\left(x^3-9x^2+26x-24\right)\)
\(=\left(x-5\right)\left(x^3-4x^2-5x^2+20x+6x-24\right)\)
\(=\left(x-5\right)\left(x-4\right)\left(x^2-5x+6\right)\)
\(=\left(x-5\right)\left(x-4\right)\left(x-3\right)\left(x-2\right)\)
\(\dfrac{9}{4}x^2-25y^2=\left(\dfrac{3}{2}x-5y\right)\left(\dfrac{3}{2}x+5y\right)\)
\(x^2-xy+\dfrac{1}{4}y^2=\left(x-\dfrac{1}{2}y\right)^2\)
a)x2-4x=x(x-4)
b)x2-5xy+x-5y=x(x-5y)+(x-5y)=(x+1)(x-5y)
c)x2-10xy-49+25y2=x2-10xy+25y2-49
=(x-5)2-72=(x-5-7)(x-5+7)
=(x-12)(x+2)
\(a,Sửa:x^2+4xy-9+4y^2=\left(x+2y\right)^2-9=\left(x+2y-3\right)\left(x+2y+3\right)\\ b,=\left(x-6y\right)^2-1=\left(x-6y-1\right)\left(x-6y+1\right)\\ c,=36-\left(x-5y\right)^2=\left(6-x+5y\right)\left(6+x-5y\right)\)
\(a,=x^2-4-x^2+2x+4=2x\\ b,=\left(x-5y\right)^2:\left(5y-x\right)=\left(5y-x\right)^2:\left(5y-x\right)=5y-x\\ c,Sửa:\left(28x-9x^2+x^3-30\right):\left(x-3\right)\\ =\left(x^3-3x^2-6x^2+18x+10x-30\right):\left(x-3\right)\\ =\left(x-3\right)\left(x^2-6x+10\right)\left(x-3\right)=x^2-6x+10\)
\(x^4-x^2+10x-25\)
\(=x^4-\left(x^2-10x+25\right)\)
\(=\left(x^2\right)^2-\left(x^2-2\cdot5\cdot x+5^2\right)\)
\(=\left(x^2\right)^2-\left(x-5\right)^2\)
\(=\left[x^2-\left(x-5\right)\right]\left[x^2+\left(x-5\right)\right]\)
\(=\left(x^2-x+5\right)\left(x^2+x-5\right)\)
a)4x2+4x+1-x2-10x-25=0
`<=>(2x+1)^2-(x+5)^2=0`
`<=>(2x+1-x-5)(2x+1+x+5)=0`
`<=>(x-4)(3x+6)=0`
`<=>(x-4)(x+2)=0`
`<=>` \(\left[ \begin{array}{l}x=2\\x=-2\end{array} \right.\)
b)(x^2+x+7)(x^2+x-7)=(x2+x)2-7x
`<=>(x^2+x)^2-7^2=(x^2+x)^2-7x`
`<=>-7^2=-7x`
`<=>-49=-7x`
`<=>x=7`
Vậy x=7